Splenic and hepatic artery aneurysm: a case report - Malo, Raúl Andrés Troya; Suárez Luna, Luis Ernesto; Gómez, Gloria Barrera; Reyes, Karina Sánchez (International Journal of Research in Medical Sciences, 2021)
Visceral artery aneurysms (VAA) have an incidence of 0.01-2% and are mainly diagnosed as an incidental finding in imaging studies done for other reasons. Their mortality when ruptured can be as high has 75%. We present a rare case of multiple visceral artery aneurysms that presented as dull abdominal pain and were managed with open surgery in accordance to specific treatment criteria.